Opportunistic Bacteria in Tonsil and Dental Plaque are Indicator for Oral Care - Nobuhiro Hanada; Chiyoko Hakuta; Ayako Okada; Kaoru Sogabe; Erika Kakuta; Keiko Endo; Susumu Imai; Masaaki Okamoto; Yoshiaki Nomura (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Background of the study: Detection of the opportunistic microorganisms can be the indicator for the oral hygiene. However, there are many sampling sites in one subject. Context and purpose of study: The purpose of this study was to evaluate the suitable sampling site for opportunistic pathogens as an indicator of the oral hygiene. Results: In the 21 healthy females' swab samples of tonsil, meticillin-sensitive Staphylococcus aureus, Pneumobacillus, Haemophilus influenzae, H. parainfluenzae, Lancefield group A streptococci, Lancefield group G streptococci, Haemophilus sp. were detected; detection rates were 33.3%, 4.8%, 19.0%, 4.8%, 4.8% and 14.3%, respectively. The detection rates of methicillin-sensitive Staphylococcus aureus and Haemophilus sp. were the highest when compared to the other sampling sites. For H. influenzae, the detection rates were relatively high; 14.3% for tongue, 38.1% for dental plaque and 52.4% for saliva. Main findings: Detections of the commensal and opportunistic pathogens from tonsil and saliva were independent. Microbial flora form nasal cavity was independent form pharynx. Conclusion: Tonsil and saliva are the suitable sampling site to detect the opportunistic pathogens for the indicator of the oral hygiene. Brief Summary: Opportunistic pathogens in tonsil or saliva can be the indicator of the oral hygiene. Potential implications of the study: For the prevention of pneumonia, oral care is useful. In this situation, MRSA, P. aeruginosa, β-hemolytic streptococci, S. marcescens, M. catarrhallis or H. influenza in tonsil or saliva can be the indicator of the oral care.